Adolescents with better mental health have less problem alcohol use six months later - Meredith, Lisa S. (Addict Behav, 2019)
PURPOSE: Adolescents who report having mental health problems, including depression and anxiety, are at greater risk of alcohol use. We examined the longitudinal association between mental health and alcohol use six months later in a diverse adolescent sample attending a primary care appointment. The primary care setting provides a unique opportunity to reach this younger age group and address risk factors, including mental health problems and substance use. METHODS: Adolescents aged 12–18 (n = 668) recruited from waiting rooms at four primary care clinics in Los Angeles, California and Pittsburgh, Pennsylvania completed a baseline web-based survey (April 2013 to November 2015) and another survey six months later. Bivariate analysis and multi-variable regression assessed associations between baseline mental health and 6-month alcohol use outcomes (any use, heavy use, and maximum quantity). RESULTS: Adolescents were stratified by mental health scores using the Mental Health Inventory-5 (MHI-5) cut off at baseline. In unadjusted analyses of alcohol outcomes at six months, adolescents with more mental health problems reported higher alcohol use across all three measures (p < .01 for heavy use; p < .05 for any use and maximum quantity used). Adolescents’ reports of better mental health at baseline were associated with fewer heavy drinking episodes (p < .05) and lower maximum number of drinks (p < .05) at six months, after adjusting for baseline alcohol use, intervention group, site, and demographic characteristics. CONCLUSIONS: Addressing mental health in primary care may be important for decreasing alcohol problems in adolescents. Strategies for facilitating screening and intervention with adolescents at-risk of alcohol use are warranted.